Association of expedited review programmes with postmarketing safety events of new drugs approved by the US food and drug administration between 2007 and 2017 - Bao Liu; Xingyue Zhu (BMJ Open)
Objective To explore the associations between the risks of postmarketing safety events of new drugs and the four expedited programmes of priority review, accelerated approval, fast track and breakthrough therapy established by the US Food and Drug Administration (FDA); and to investigate whether multiple uses of expedited programmes, and the combinations of expedited programmes with orphan designation, were relevant to different safety profiles.Design Cohort study.Setting USA.Participants All new drugs approved by the FDA between 1 January 2007 and 31 December 2017, followed up until 10 April 2021.Outcome measures Safety events included safety-related withdrawal, new boxed warning, drug safety communication, postapproval risk evaluation mitigation strategy and safety-related labelling changes. The duration from marketing approval to the occurrence of a safety event was measured.Method Cox models were performed to determine the factors related to the time-to-safety event.Results The FDA approved 338 new drugs between 2007 and 2017, among which 53.6% (181) were under expedited review and 32.2% (109) received two or more expedited programmes. It took median time of 1.75 years (IQR 1.10–2.93) and 2.31 years (IQR 1.33–4.21), respectively, for new drugs to be observed of their first event and first serious event. The raised risk for first safety event was found to associate with breakthrough therapy (adjusted HR 1.83; 95% CI 1.21 to 2.77; p=0.004), and with the combination of accelerated approval with orphan designation (adjusted HR 2.84; 95% CI 1.12 to 7.23; p=0.028). Triple or more use of expedited programmes correlated with higher risk for first serious event (adjusted HR 4.16; 95% CI 1.69 to 10.22; p=0.002).Conclusions The increased risks of the breakthrough therapies, accelerated orphan drugs and triple or more use of expedited programmes indicated the necessity for intensive postmarketing risk surveillance.